Avaliação da influência de polimorfismos gênicos em voluntários de um estudo de bioequivalência entre duas formulações de varfarina - Cláudia de Souza Pedrosa (2012)
The standard single dose 2x2 crossover bioequivalence study is routinely used to determine the interchangeability of reference drugs and generic products. It’s also known that individual variability of participating volunteers in relation to drug kinetic parameters is a factor which impacts the cho ice of study design to be conducted. In this work the polymorphisms of CYP2C9 e VKORC1 genotypes were determined in 31 volunteers participating in a study matching two warfarin formulations. The impact of drug biotransformation and the single results of the polymorphisms of the volunteers within the investigation of bioequivalence were assessed through the results of this kinetic study. Thus, a bioanalytical method was developed and validated aimed at the quantitation of warfarin in human plasma at different time sampling. The different polymorphisms of the abovementioned genotypes were also assessed in volunteers participating in the comparative bioequivalence study. The high performance liquid chromatography coupled to mass spectrometry analysis were performed using NovaPak C18 column (150 mm x 3.9 mm), maintained at 30ºC. The mobile phase was composed of acetonitrile:water (80:20, v/v) plus formic acid and ammonia solution, at a 0.600 mL/min flow rate. The typical retention times for warfarin and p-chloro-warfarin (internal standard) were 2.24 and 2.42 minutes, respectively. The mass spectrometer equipped with positive electrospray source was used in multiple reaction monitoring (MRM) mode, in order to monitor the 309.2>163.0 and 342.9>162.8 transitions for both the analyte and internal standard. The proposed method for results quantification demonstrated a significant correlation of the results (r=0.999541) within concentration ranging from 5.0 to 1000.0 ng/mL. PCR and real-time PCR techniques were employed to determine the polymorphisms of CYP2C9 and VKORC1 genotypes. Seven volunteers were found with mutant for gen CYP2C9 with allels *2 or *3, and four others were found with mutants for gen VKORC1with polymorphisms AA. A comparative assessment of the formulations was performed by means of the construction of bioequivalence intervals. There were three comparisons, one of which considering all the volunteers, and two more considering only the wild volunteers for the polymorphisms of both CYP2C9 and VKORC1. The results indicate that, for these volunteers, mutant polymorphisms did not affect bioequivalence completion, since the conclusion headed towards bioequivalence between the formulations considering all the calculated bioequivalence intervals.